ANALYZING YOUNG LEARNERS’ ORAL NARRATIVES THROUGH SYSTEMIC FUNCTIONAL LINGUISTICS - Arso Setyaji; Jafar Sodiq (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
Oral narrative ability plays a pivotal role in children’s language development, yet studies in EFL settings have seldom examined how young learners construct meaning through functional and curriculum-based perspectives, and drawing on Halliday’s three metafunctions, namely, ideational, interpersonal, and textual. The study analyzes the oral presentations of six 9-10-year-old young learners in a private primary school in Semarang, Central Java, Indonesia, completing a classroom narrative assignment titled “A Day in My Life”. The data consisted of audio recordings of students' storytelling, which were transcribed and analyzed using metafunctional categories: process types, mood structures, modality, and thematic organization. The analysis reveals how children’s language choices reflect emerging narrative competence, social identity, and classroom positioning. While most narratives followed predictable patterns with material processes and simple themes, some learners exhibited agentive voice, evaluative stance, and interpersonal variation. This qualitative inquiry demonstrates how the combined application of SFL can uncover subtle layers of meaning in children’s oral narratives, yielding pedagogical insights for narrative instruction and deepening understanding of language development in EFL contexts.